2010
DOI: 10.1111/j.1530-0277.2010.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Period 2 Gene Deletion Abolishes β‐Endorphin Neuronal Response to Ethanol

Abstract: Background Ethanol exposure during early life has been shown to permanently alter the circadian expression of clock regulatory genes and the β-endorphin precursor proopiomelanocortin (POMC) gene in the hypothalamus. Ethanol also alters the stress- and immune-regulatory functions of β-endorphin neurons in laboratory rodents. Our aim was to determine whether the circadian clock regulatory Per2 gene modulates the action of ethanol on β-endorphin neurons in mice. Methods Per2 mutant (mPer2Brdml) and wild type (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 54 publications
2
23
0
Order By: Relevance
“…Both male and female mice display escalated alcohol intake after 3 weeks of chronic IA exposure, mainly occurring at the first 4-hour dark cycle (25-30% in total daily intake), without much change in the other two-time periods [Zhou et al, 2017a, b]. Of interest, hypothalamic POMC deficient mice displayed lower alcohol intake than wild-type mice during the first 4-hour dark cycle in both sexes [Zhou et al, 2017b], suggesting a potential contribution of hypothalamic POMC to the genetically determined tendency of hypothalamic POMC deficient mice towards reduced alcohol consumption, with potential clock genes' influence, as found in other studies with alcohol [Spanagel et al, 2005;Agapito et al, 2010;Partonen, 2015].…”
Section: Pro-opiomelanocortin (Pomc)/β-endorphin and Mu-opioid Rementioning
confidence: 80%
“…Both male and female mice display escalated alcohol intake after 3 weeks of chronic IA exposure, mainly occurring at the first 4-hour dark cycle (25-30% in total daily intake), without much change in the other two-time periods [Zhou et al, 2017a, b]. Of interest, hypothalamic POMC deficient mice displayed lower alcohol intake than wild-type mice during the first 4-hour dark cycle in both sexes [Zhou et al, 2017b], suggesting a potential contribution of hypothalamic POMC to the genetically determined tendency of hypothalamic POMC deficient mice towards reduced alcohol consumption, with potential clock genes' influence, as found in other studies with alcohol [Spanagel et al, 2005;Agapito et al, 2010;Partonen, 2015].…”
Section: Pro-opiomelanocortin (Pomc)/β-endorphin and Mu-opioid Rementioning
confidence: 80%
“…Since there is distinct temporal variation and pronounced expression differences of Per2 across the life span (Figure 2) indicating temporal and regional-specific regulatory mechanisms, these results do not rule out a role of SNP rs56013859 or perhaps rare or intermediate variants in linkage disequilibrium with this SNP in transcriptional regulation. Recently, Agapito et al [36] demonstrated a PER2 mutation in mice to be associated with the regulation of β-endorphin release to acute and chronic ethanol challenges, providing another clue to the mechanism of different effectiveness of alcohol drinking as a means to cope with life events.…”
Section: Discussionmentioning
confidence: 99%
“…In the mediobasal hypothalamus, the overall expression levels and rhythm amplitudes of Per1 and Per2 were significantly reduced in animals exposed to alcohol during early development (Agapito, Barreira, Logan, & Sarkar, 2012; Chen, Kuhn, Advis, & Sarkar, 2006). The lack of Per2 reduced the stimulatory response of ethanol on hypothalamic genes and neuropeptides involved in metabolism and stress regulation (Agapito et al, 2010). Developmental alcohol exposure may alter Per2 expression and subsequent downstream pathways by a number of molecular mechanisms, such as accelerating degradation by CK1ε and epigenetic modifications.…”
Section: The Effects Of Drugs Of Abuse On Circadian Rhythms and Circamentioning
confidence: 99%